Assessing the Digital Information Literacy Levels among Students in Higher Education - Uzma; Nasreen, Shariqa (Annals of Human and Social Sciences, 2024)
The impact of digital information literacy on students is a critical area of study in today's technology-driven educational landscape. This research explores how digital literacy influences student learning, research capabilities, and overall academic performance. By assessing students' proficiency in utilizing digital tools, hardware, software, and the internet, the study aims to identify the benefits and challenges associated with digital information literacy.Quantitative data is collected through a multi-stage stratified sampling technique, using standardized scales to evaluate students' digital literacy levels. The data is analyzed using Three-Way ANOVA and correlation to uncover significant patterns and relationships. The findings of this research are valuable for enhancing digital literacy education, thereby improving students' academic success and research skills. By understanding the current state of digital information literacy and the obstacles to its adoption, educational institutions can develop more effective strategies and curricula. This study not only highlights the importance of digital literacy in the modern academic environment but also offers recommendations for facilitating its widespread adoption among students, ensuring they are well-equipped for the demands of the digital age.